Comprehensive Ultrasound Diagnosis of Sigmoid Diverticulitis - A. I. Кoushnerou; I. A. Hadji-Ismail; A. V. Vorobei; S. I. Rudenka (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A definition and systematisation of sigmoid diverticulitis semiotics in a comprehensive ultrasonic check-up for early illness diagnosis.Materials and methods. Ultrasound examination data on 64 patients with sigmoid diverticulum have been analysed. The primary visit reason was recurrent varying-intensity pain in left abdominal quadrant, unstable stool and flatulence. The patients were 28 (43.75%) men and 36 (56.25%) women aged 38–85 years, mean age 55.6 years; 31 (48.44%) were diagnosed with diverticulitis. We used the HD15 (Philips, the Netherlands), HS 60 (Samsung, South Korea) and Hi Vision Preirus (Hitachi, Japan) ultrasound instruments equipped with convex and intracavitary microconvex 2–12 MHz linear transducers. Patients were examined on an empty stomach and unprepared intestine. Colon and rectum were explored at different approaches, transabdominally, transperineally, transrectally and transvaginallyResults. The findings laid out a more elaborated ultrasound semiotics of diverticulitis. Ultrasound check-up enables a reliable estimation of blood supply and peristalsis, colonic wall thickness and layers, presence of asymptomatic diverticula, signs of acute diverticulitis (pain on sensor touch, mesocolic tissue infiltration, presence of faecal calculi and gas in diverticulum, peridiverticulitis) and other complications of diverticular disease (fistulae, abscess or peritonitis), as well as a consistent differential instrumental diagnosis of other organ illnesses.Conclusion. Ultrasound is an indispensable supplement in clinical diagnosis of diverticula, diverticulitis and their complications in the cases when other methods like X-ray, CT or colonoscopy are contraindicated.